Effectiveness Test of Sedap Malam Flower Extract (Polianthes tuberosa) Against Motality of House Fly (Musca domestica): Uji Efektivitas Ekstrak Bunga Sedap Malam (Polianthes tuberosa) Terhadap Motalitas Lalat Rumah (Musca domestica) - Rani, Maghfiroh Ramadhani; Ardiansyah, Syahrul (Universitas Muhammadiyah Sidoarjo, 2020)
Diarrhea is a disease caused by the house fly insect (Musca domestica). It is necessary to do alternatives using natural ingredients as house fly repellent (Musca domestica), one of which is tuberose extract (Polianthes tuberosa). Ethanol extract of tuberose flower has Eugenol compound which can be used as an insecticide. This research was conducted to determine the toxic effect of tuberose extract (Polianthes tuberosa) on the mortality of house fly (Musca domestica). This research is an experimental study (experimental) and Completely Randomized Design Test (CRD) by conducting 6 treatment groups including negative control (aquades) and tuberose flower extract concentrations of 10%, 20%, 30%, 40%, and 50%. The data obtained for 72 hours were analyzed by using the One Way ANOVA statistical test, a significance value of P = 0.000 (p<0.005) was obtained and continued with the probit test, it can be said that tuberose bug extract has a toxic effect on house flies with LC50 at a concentration of 45.808%.